ANALISIS BEBAN KERJA FISIK DALAM PENENTUAN WAKTU ISTIRAHAT PADA KARYAWAN WELDER PADA PT MCDERMOT INDONESIA - Dominggus Awola, Fernando; Zetli, Sri (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the physical workload and determine the optimal rest time for welders at PT McDermott Indonesia using a physiological approach. Workload was measured through the Cardiovascular Load (CVL) method and energy consumption based on heart rates during work. The results showed that %CVL ranged from 30%–59%, categorized as